Enteric glial cells aggravate the intestinal epithelial barrier damage by secreting S100β under high-altitude conditions - Huichao Xie; Xiong Zeng; Wensheng Wang; Wei Wang; Ben Han; QianShan Tan; Qiu Hu; Xingyu Liu; Shuaishuai Chen; Jun Chen; Lihua Sun; Yihui Chen; et al. (Molecular Biomedicine, 2023)
Abstract Damage to the intestinal epithelial barrier (IEB) has been reported under high-altitude (HA) conditions and may be responsible for HA-associated gastrointestinal (GI) disorders. However, this pathogenetic mechanism does not fully explain the GI stress symptoms, such as flatulence and motility diarrhea, which accompany the IEB damage under HA conditions, especially for the people exposed to HA acutely. In the present study, we collected the blood samples from the people who lived at HA and found the concentration of enteric glial cells (EGCs)-associated biomarkers increased significantly. HA mouse model was then established and the results revealed that EGCs were involved in IEB damage. Zona occludens (ZO)-1, occludin, and claudin-1 expression was negatively correlated with that of glial fibrillary acidic protein (GFAP) and S100β under HA conditions. In order to learn more about how EGCs influence IEB, the in vitro EGC and MODE-K hypoxia experiments that used hypoxic stimulation for simulating in vivo exposure to HA was performed. We found that hypoxia increased S100β secretion in EGCs. And MODE-K cells cultured in medium conditioned by hypoxic EGCs showed low ZO-1, occludin, and claudin-1 levels of expression. Furthermore, treatment of MODE-K cells with recombinant mouse S100β resulted in diminished levels of ZO-1, occludin, and claudin-1 expression. Thus, HA exposure induces greater S100β secretion by EGCs, which aggravates the damage to the IEB. This study has revealed a novel mechanism of IEB damage under HA conditions, and suggest that EGCs may constitute a fresh avenue for the avoidance of GI disorders at HA.